The Influence of Quality of Measles Vaccine to The Incidence of Measles in Pasuruan Regency - Dwi Wahyu Ningtyas; Arief Wibowo (Universitas Airlangga, 2015)
Measles is the main cause of child mortality among vaccine-preventable disease (PD3I). Measles in the Pasuruan Regency in 2014 reached 199 cases. Measles does not only occur in areas with low immunization coverage but also in areas with high immunization coverage. This can be caused by the quality of the vaccine given is poor, so it does not provide protection against measles. This study aims to influence the quality of the measles vaccine on the incidence of measles in the Pasuruan District. This research is an observational analytic study with a case-control approach. Case samples were 30 villages that had measles cases in 2014, and control samples were 30 villages that did not have measles cases in 2014. Data were analyzed using linear regression and logistic regression tests. The results of this study include training (p = 0.002), knowledge (p = 0,000), and availability of vaccine facilities (p = 0.022) affecting the quality of the measles vaccine, and the quality of measles vaccine (p = 0.008) influencing the incidence of measles. Conclusions in this study include the influence of knowledge on the quality of the measles vaccine, there is an influence between the quality of the vaccine on the incidence of measles in the Pasuruan District. Based on the results of the research, the advice that can be given is expected to be an increase in the knowledge of officers related to the quality of measles vaccines, for example by assisting, and requiring officers to use immunization facilities and infrastructure in accordance with Standard Operating Procedures (SOP).